920 MHz ultra-high field NMR approaches to structural glycobiology - Kato, Koichi; Sasakawa, Hiroaki; Kamiya, Yukiko; Utsumi, Maho; Nakano, Michiko; Takahashi, Noriko; Yamaguchi, Yoshiki (Biochimica et biophysica acta, 2008)
Although NMR spectroscopy has great potential to provide us with detailed structural information on oligosaccharides and glycoconjugates, the carbohydrate NMR analyses have been hampered by the severe spectral overlapping and the insufficiency of the conformational restraints. Recently, ultra-high field NMR spectrometers have become available for applications to structural analyses of biological macromolecules. Here we demonstrate that ultra-high fields offer not only increases in sensitivity and chemical shift dispersion but also potential benefits for providing unique information on chemical exchange and relaxation, by displaying NMR spectral data of oligosaccharide, glycoprotein, and glycolipid systems recorded at a 21.6 T magnetic field (corresponding to 920 MHz 1H observation frequency). The ultra-high field NMR spectroscopy combined with sugar library and stable-isotope labeling approaches will open new horizons in structural glycobiology.